Tanggung Gugat Resiko Dalam Aspek Hukum Kesehatan - Arman Anwar (Faculty of Law, Universitas Pattimura, 2017)
Health is a fundamental need for every human being in his life and to meet these needs the role of doctors and health workers is very important. Doctors and Health care in providing health services to the community is always required in order to provide the best service. So with the Hospital. However, the health services provided may result in two different possibilities of the patient being cured or even worsening the disease until death. If the patient recovers it will flow millions of praise and abundant various forms of appreciation that he receives but if that happens is the opposite then in certain conditions where the patient feels aggrieved can culminate until the lawsuit to court. In medical practice, doctors do not work alone but are also often assisted by other health workers. Likewise Hospital as a corporation employs doctors and health workers to provide health services to the community. If in the event of any medical treatment from medical personnel to medical personnel and/or Hospital to the physician and at risk of mistake or negligence in the health service, then the loss suffered by the patient may result in risks (risico aanspraklijkheid) based on Article 1367 paragraph (3) BW. In the context of health law regulated in Article 65 of Law Number 36 Year 2014 on Health Personnel, and Article 35 Paragraph 6 of Law Number 38 Year 2014 on Nursing and Article 23 Paragraph (3) point c Regulation of the Minister of Health of the Republic of Indonesia No. 2052 / Menkes / Per / X / 2011 About Practice License and Implementation of Medical Practice as well as Article 46 Act Number 44 of 2009 About Hospital that is Hospital is legally responsible for all the losses caused by negligence made by health personnel in the Hospital. Efforts to prevent it internally need to agree on the rights and obligations of each party in a specified standard of conduct that is proportionally regulated and based on equitability values, either in the form of Hospital by Law as well as the prevailing rules binding on all staff within a hospital staff (Medical staff by law).